Lots of Comments on The Monuments of Eilatan-Oktom Culture (On the Example of Burial-Mounds) - A.A.Alokhunov (Research Parks Publishers, 2021)
The article briefly describes the history of the study of Mazar-kurgans belonging to the early Iron Age of Eilatan-Aktam culture, which provide an idea of the material culture and funeral rites of the population of the Fergana Valley of this period.